PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA SEKOLAH DASAR BERBASIS STEAM TERINTEGRASI BUDAYA LOKAL - Nurmita Mita; Fira Trizki Ragitha; Nurlaylla Afdar Agustin; Della Okta Rinanda; Dyah Rahayuningtyaswara (Jurnal Genta Mulia, 2026)
This study aims to develop an elementary mathematics learning media based on STEAM integrated with Lampung local culture. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The participants were fourth-grade students at UPT SD Negeri 2 Margodadi, Pringsewu Regency. Data were collected through expert validation sheets, student response questionnaires, and learning achievement tests. The validation results showed an average feasibility percentage of 90%, categorized as very feasible. The implementation test revealed that students’ mastery level reached 90.47%, and the average student response was 93%, also categorized as very feasible. The developed learning media effectively improved students’ understanding of through activities integrating science, technology, engineering, arts, and mathematics within a local cultural context. Thus, STEAM-based learning media integrated with local culture not only enhance mathematical learning outcomes but also strengthen character values and students’ appreciation of their regional culture.